Efektivitas Pembelajaran Bagi Murid Di Madrasah Ibtidaiyah - Hanifa, Millata; Permana, Rusma; Ulfah, Miftahul (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2021)
The existence of madrasah ibtidaiyah is equivalent to elementary school as part of basic education. The core activity of a school or madrasa is learning. Children enrolled by their parents in the madrasah ibtidaiyah are so that children can easily learn a number of important basic subjects so that children become pious children. In other words, children who learn will become adults, because they master a number of subjects, or the knowledge needed according to the curriculum to live in society, or continue to higher education. For this reason the effectiveness of learning becomes the teacher’s task, because it requires professional teachers who are able to realize successful learning, especially seen from changes in student behavior, both cognitive, affective, and psychomotor.